Identification of Phytochemical Compounds of Noni Leaf Extract (Morinda Citrifolia) and Its Activity in Increasing Leukemia Cell Apoptosis - Wati, Diana Rahma; Robi’ah; Purnamasari, Risa; Agustina, Eva; Lusiana, Nova; Hidayati, Irul; Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2025)
Leukemia is a blood cancer characterized by overgrowth of abnormal white blood cells due to disruption of the apoptosis process, which is cell death that controls the number of cells in the body. This malignancy causes the accumulation of cancer cells that damage normal tissues and disrupt the immune system. One of the plants that can stimulate apoptosis and inhibit the development of blood cancer cells is noni leaves. Noni (Morinda citrifolia) leaves are known to contain antioxidant compounds such as flavonoids, phenols, and saponins that play a role in neutralizing DNA damage and supporting apoptosis mechanisms. This study aims to identify the phytochemical content of noni leaf extract and review its potential activity in increasing leukemia cell apoptosis. The extraction process was carried out by maceration method using ethanol solvent, then the extraction results were tested phytochemically to determine the content of active compounds such as alkaloids, flavonoids, tannins, saponins, and phenolics. The results of the phytochemical test showed that noni leaf extract was positive for flavonoids, saponins, and phenolics which are known to have antioxidant, cytotoxic, and apoptosis induction activities.